Hybridization versus conservation: are domestic cats threatening the genetic integrity of wildcats (Felis silvestris silvestris) in Iberian Peninsula? - Oliveira, Rita (The Royal Society, 2008)
Cross-breeding between wild and free-ranging domestic species is one of the main conservation problems for some threatened species. The situation of wildcats (Felis silvestris silvestris) in Europe is a good example of this critical phenomenon. Extensive hybridization was described in Hungary and Scotland, contrasting with occasional interbreeding in Italy and Germany. First analyses in Portugal revealed a clear genetic differentiation between wild and domestic cats; however, four hybrids were detected. Here, we extended the approach to Iberian Peninsula using multivariate and Bayesian analyses of multilocus genotypes for 44 Portuguese wildcats, 31 Spanish wildcats and 109 domestic cats. Globally, wild and domestic cats were significantly differentiated (F(ST)=0.20, p<0.001) and clustered into two discrete groups. Diverse clustering methods and assignment criteria identified an additional hybrid in Portugal, performing a total of five admixed individuals. The power of admixture analyses was assessed by simulating hybrid genotypes, which revealed that used microsatellites were able to detect 100, 91 and 85% of first-generation hybrids, second-generation genotypes and backcrosses, respectively. These findings suggest that the true proportion of admixture can be higher than the value estimated in this study and that the improvement of genetic tools for hybrids detection is crucial for wildcat conservation.